Success determinants of open innovation partnerships between car manufacturers and start-ups in Germany / Elisabeth Stache, Georg Hauer and Patrick Harte - Stache, Elisabeth; Hauer, Georg; Harte, Patrick (Universiti Teknologi MARA, 2022)
In a context of saturated markets, increasing price pressure, growing competition, changing preferences and consumption patterns, the automotive industry is evolving into a diversified mobility industry. This disruptive transformation challenges German car manufacturers to reinvent themselves and innovate in diverse directions. Since loose open-innovation (OI) partnerships with start-ups offer manufacturers not only flexibility but, more importantly, cutting-edge expertise from outside the traditional industry, they have become the partner of choice since 2010. Although incumbent-start-up partnerships are on the rise, the current literature scarcely addresses the challenges that arise from innovation cooperation with such disparate partners. Therefore, this study attempts to identify the success determinants to provide practitioners with guidance and contribute to close current gaps in literature. Based on a qualitative research design, in form of semi-structured expert interviews, key barriers and drivers concerning leadership, work methods, culture and intellectual property were identified. Considering the start-up´s, the incumbent´s and the interface´s perspectives, the paper provides a conceptual framework that illustrates the interrelations and challenges in open innovation partnerships. The start-up´s group expertise and maturity turned out to be a major driver for initiating collaboration. The key collaborative success drivers are agile work methods, the group´s internal cultural transformation, the interface´s autonomy, and a solid level of trust and openness between the involved parties. Besides practical recommendations, derived by the identified success factors, the paper constitutes a theoretical basis for further research